Erector Spinae Plane Block for Different Laparoscopic Abdominal Surgeries: Case Series - Tulgar, Serkan (Case Rep Anesthesiol, 2018)
The ultrasound guided erector spinae plane (ESP) block is a recent block described for various surgeries for postoperative analgesia. ESP block has effect on both visceral and somatic pain; therefore, its use in laparoscopic cholecystectomy and other abdominal surgeries can be advantageous. We describe successful ESP block application in three different cases for postoperative pain. Two patient were operated on using endoscopic retrograde cholangiopancreatography and laparoscopic cholecystectomy and one patient was operated on using laparoscopic cholecystectomy together with the inguinal hernia operation.